2020
DOI: 10.21608/jpp.2020.79106
|View full text |Cite
|
Sign up to set email alerts
|

Determination Critical Periods of Weed Competition and Weed Control Influence on Yield Productivity of Sweet Pepper (Capsicum annuum L.)

Abstract: Field experiments were carried out at Sids Research Station, Agricultural Research Center during 2016 and 2017seasons to determine the critical period of weed competition in pepper yield and study the effect of some pre-emergence herbicides on controlling weeds and its reflection on yield and its component of pepper. It could be concluded that some safe alternatives to mechanical weed control hand hoeing (twice), are the use of mulching by black polyethylene or reduced rate of pendimethalin (0.850 L.\fed) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…Stomp extra and Aemx being dinitroaniline, are known to be absorbed by germinating weed seedlings and inhibits cell division in meristematic tissue so that most of weeds die within few days of their emergence. These results are in agreement with obtained by Nagar et al (2009) Yadav et a.l (2015), Galal et al (2019) and Galal et al (2020). Savaliya et al (2017) reported that the highest weed control efficiency were registered under treatments of two hand weeding at 20 and 40 days after sowing and pendimethalin at 1.0 kg/ha as pre-emergence + quizalofop ethyl 0.04 kg/ha at 20 days after sowing 85.3 and 79.3%, respectively.…”
Section: Statisticale Analysissupporting
confidence: 93%
See 3 more Smart Citations
“…Stomp extra and Aemx being dinitroaniline, are known to be absorbed by germinating weed seedlings and inhibits cell division in meristematic tissue so that most of weeds die within few days of their emergence. These results are in agreement with obtained by Nagar et al (2009) Yadav et a.l (2015), Galal et al (2019) and Galal et al (2020). Savaliya et al (2017) reported that the highest weed control efficiency were registered under treatments of two hand weeding at 20 and 40 days after sowing and pendimethalin at 1.0 kg/ha as pre-emergence + quizalofop ethyl 0.04 kg/ha at 20 days after sowing 85.3 and 79.3%, respectively.…”
Section: Statisticale Analysissupporting
confidence: 93%
“…which recorded increase in seed yield which determined by 230.2, 222.3, 202.6 and 200.9% & 224.8, 216.0, 207.8 and 206.1 % , and increases in net income LE per feddan by 7050, 5130, 4350 and 5630, & 7600, 6560, 5775 and 7075, and highest gross income by 20850, 20130, 18350 and 18180, & 21400, 20560, 19775 and 19625, and increases in benefit/costs ratio to 1.51, 1.34, 1.31 and 1.45 & 1.55, 1.47, 1.41 and 1.56 in 2016/2017 and 2017/2018 than unweeded check respectively, meanwhile the benefit / costs ratio in unweeded check were minus than one in both seasons. These results are in agreement, Kushwaha et al (2002) Savaliya et al (2017) Yadav et al (2013, Gasti and Chakravorty (2019), Galal et al (2019) and Galal et al (2020). Note that the prices are approximate in the two seasons for costs and gross.…”
Section: D:correlation Coefficients Between Weed Categories and Coriasupporting
confidence: 89%
See 2 more Smart Citations